Periurethral Cleaning Solution against Bacteria Colonization Count in the Periurethral Area Prior to Urinary Catheterization - Kristina Lisum; Ni Luh Widani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
Introduction: Patient safety is an important element that must be noted when providing care to patients, including by the nurse. The purpose of this study was to compare the effectiveness of cleaning periurethral with povidone iodine 10 %, povidone iodine 2% and normal saline against bacteria colonization before catheterization. Methods: This study used a quasi-experimental pre- and post-intervention design with a control group. Periurethral swabs were obtained from a total of 60 patients (povidone iodine 10 % as a control group, 20; povidone iodine 2%, 20; normal saline, 20). Results: Through a paired t-test, it can be seen that there was a significant decrease (p-value: 0.00; p < 0.05) in the bacteria colonization count using povidone iodine 2% and normal saline. When using povidone iodine 10% , there was no significant decrease (p-value: 0.55; p >.05) in the bacterial colonization count. Discussion: Povidone-iodine 2% is the most effective solution for us to reduce bacterial colonization in the periurethral area rather than another solution. The recommendation is to test for bacteria colonization in the urine culture using the different periurethral cleaning solutions.